HIGH RISK PREGNANCY IN WOMEN WITH PREVIOUS C-SECTION AND SHORT INTERVAL PREGNANCY: CASE REPORT - Sekar Putri Kirana Koerniawan; Ratna Dwi Jayanti; Farida Fitriana (UNIVERSITAS AIRLANGGA, 2023)
The main risk in pregnancies occur at 4T (too many, too young, too old, and too close birth spacing). The distance between the previous delivery and the next pregnancy and the previous method of delivery are two of the many other factors that affect the condition of the mother and the fetus that will be born later. This case report aims to analyze the effect of spacing between the last child and history of previous births on the outcome of the mother and her baby. This report describes data on pregnant women participating in the Continuity of Care (CoC) program. The results show that the outcomes obtained by the mother in this second delivery are within normal limits. However, this does not mean the possibility for pregnancies that are not planned properly to cause events that are detrimental to the mother and fetus are none.